Key Factors Influencing Job Selection Among Generation Z in Thailand - Niyomsujarit, Keschadaporn; Na Keeree, Pratsanee (Journal for Strategy and Enterprise Competitiveness, 2025)
This study aims to examine the factors influencing job application decisions among Generation Z, using motivational factors, work support factors, and organizational culture factors as independent variables. Multiple Linear Regression analysis was employed to analyze data collected from a sample of 400 individuals. The findings reveal that the motivational factors significantly influencing job application decisions include job responsibility (β = 0.174, Sig. = 0.007) and work success (β = 0.173, Sig. = 0.003). As for work support factors, the organization’s reputation (β = 0.309, Sig. = 0.000) and coworker relationships (β = 0.166, Sig. = 0.001) were found to have a significant impact on job selection. In terms of organizational culture, the characteristics of organizational culture (β = 0.284, Sig. = 0.000) and the organization’s policies, vision, and mission (β = 0.208, Sig. = 0.001) positively influenced job application decisions. The research findings suggest that motivational factors explain 45.30% of the variance in job application decisions (R² = 0.453), while work support factors have the greatest influence, explaining 59.20% of the behavior (R² = 0.592). Organizational culture factors also have a strong impact, explaining 55.60% of the variance (R² = 0.556). These results highlight that Generation Z places significant importance on the organization’s reputation, workplace relationships, and alignment with organizational values. Organizations seeking to attract and retain young talent in the long term should prioritize these factors in order to create a work environment that genuinely meets the expectations and motivations of this new workforce